2017
DOI: 10.1177/1352458517692420
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptives and MS disease activity in a contemporary real-world cohort

Abstract: These observations provide reassurance for women newly diagnosed that OC use, past or current, does not appear to be associated with greater risk of relapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
(25 reference statements)
3
14
0
Order By: Relevance
“…However, in individuals carrying the major E3/E3 phenotype, EDSS and MSSS were significant lower in the OC+ group, when compared to OC– patients. In line with previous retrospective work (6, 7) and a recent longitudinal study (22) no influence of OC use on relapse risk was observed. Future research in a larger population of carriers of the ε2 and ε4 alleles is needed.…”
Section: Discussionsupporting
confidence: 90%
“…However, in individuals carrying the major E3/E3 phenotype, EDSS and MSSS were significant lower in the OC+ group, when compared to OC– patients. In line with previous retrospective work (6, 7) and a recent longitudinal study (22) no influence of OC use on relapse risk was observed. Future research in a larger population of carriers of the ε2 and ε4 alleles is needed.…”
Section: Discussionsupporting
confidence: 90%
“…DMTs do not appear to decrease the effectiveness of hormonal contraception although formal drug-drug interaction studies are limited [29]. Some studies have demonstrated that the use of oral contraceptives (OC) does not affect the disease course [30,31]. In a Portuguese cohort of 132 women a lower EDSS and milder disease severity measured by the Multiple Sclerosis Severity Score (MSSS) were found in women who used OC after disease onset (41%) compared with neverusers and past-users (discontinued OC before onset) [32].…”
Section: Use Of Contraceptivesmentioning
confidence: 99%
“…In experimental autoimmune encephalomyelitis (EAE) models, administration of estriol improved EAE, which correlated with a decrease in the number of CNS inflammatory cells [8]. However, retrospective and prospective studies have reported mixed results regarding oral contraceptive (OC) use and MS risk [10,11,12] and have reported a positive influence on relapse rates [13]. While Hellwig et al found that OC use was associated with a slightly increased risk of MS/clinically isolated syndrome (CIS) (adjusted odds ratio (OR) = 1.52, 95% CI = 1.21–1.91; p < 0.001) [12], the risk did not change with duration of OC use, suggesting non-causal association.…”
Section: Pre-pregnancymentioning
confidence: 99%
“…Additionally, age of MS onset increased with increasing time of OC use prior to MS onset [10]. Bove et al evaluated effects of past-, current- or never-OC use in women with new onset relapsing remitting multiple sclerosis (RRMS) or CIS started on a first-line injectable disease-modifying therapy and found that past OC users had a statistically significant lower annualized relapse rate (ARR) compared to never OC users (Relative Risk (RR) = 0.64, p = 0.031) and that current OC users had a non-statistically significant lower ARR compared to never OC users (RR = 0.97, p = 0.91) [13].…”
Section: Pre-pregnancymentioning
confidence: 99%
See 1 more Smart Citation